(untitled) (Research, Society and Development, 2021)
The present work discusses the psychological therapeutic approaches in the quality of life of the autistic, its general objective is to verify the therapeutic approaches used by the psychologist, which contribute to a better quality of life for the autistic. The research points,in its specific objectives, models and / or strategies to present the interventions used by psychologists with autism; identify the characteristics of the interventions carried out by the approaches, Cognitive Behavioral Therapy (CBT), Applied Behavior Analysis (ABA), Humanistic and Phenomenological Approaches and Psychoanalysis and analyze the effectiveness of psychological approaches in clinical follow-up and in the quality of life of autistic people. Interventions and therapeutic approaches aim toreduce impairment, helping individuals to overcome this difficulty. A narrative literature review (RNL) was carried out, using books, theses, as well as articles in the years (2015-2020) from the databases of the Scientific Electronic Library Online - Scielo, Latin American and Caribbean Literature in Sciences of Health (LILACS) and MED LINE (Medical Literature Analysis and Retrieval System On Line) in Portuguese, English and Spanish in search of relevant publications that discuss the subject of fundamental interest, which is, autism, psychology, therapeutic approaches and quality of life. life. In view of the above, it is concluded that there is a wide field of technical approaches, it is emphasized that, in the case of autism, greater directivity is required from the psychotherapist, with the aim of offering intervention proposals that encourage, as far as possible, the child’s compromised contact process.